Harnessing the Tet-Off system for effective gene silencing in Magnaporthe oryzae - Fang, Zhenyu; Yang, Fan; Ma, Yongge; Cai, Yan; Chen, Xin; Yang, Shiyu; Saddeeq, Abubakar Yakubu; Wang, Zonghua; Naqvi, Naweed I.; Zheng, Wenhui (Frontiers in Plant Science, 2025)
Rice blast is the most serious fungal disease affecting rice production worldwide. Studying gene function in the rice-blast fungus Magnaporthe oryzae often presents significant challenges, especially if it involves loci that are essential for the fungal growth and/or viability. Researchers expend considerable effort on the knockout process, only to find their attempts end up in vain. To address this, we introduced a transcriptional regulation system based on the Tet-Off system, designed to conditionally and effectively inhibit the expression of target genes using a tetracycline-controlled module in M. oryzae. Using Agrobacterium tumefaciens mediated-transformation, a Tet-Off cassette was first inserted upstream of the target gene. Stable transformants were obtained in which the gene expression was significantly reduced in the presence of doxycycline. We successfully generated the Tet-Off system to silence two categories of genes—those leading to mild or to severe defects in hyphal growth —demonstrating its effectiveness for functional study of genes that are critical for fungal growth, including essential genes. Additionally, the Tet-Off system, when combined with various fusion tags, enabled effective monitoring of target gene expression and protein localization. This system thus provides a robust and powerful tool for analyzing gene function in fungi without the need for complete gene deletion analysis, and thus is applicable to essential genes in M. oryzae, deepening our understanding of their roles in fungal development and pathogenesis.